2001
DOI: 10.1007/s003950170058
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of smooth muscle cell proliferation after local drug delivery of the antimitotic drug paclitaxel using a porous balloon catheter

Abstract: Percutaneous transluminal coronary angioplasty is an accepted treatment for coronary artery disease. The major limitation, however, is the high incidence of restenosis which limits the long-term benefit of this intervention. Paclitaxel is a new antiproliferative agent that has generated considerable scientific interest since it was introduced in clinical trials in the early 1980s. Recent in vitro studies have shown that paclitaxel has considerable antiproliferative activity in human coculture systems. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…DCB are becoming a promising endovascular tool, because they have the capacity of local drug transfer to the vessel wall, inhibiting cell proliferation and moderating the hypertrophic cell response to injury [6]. An additional benefit of DCB is that they do not leave any foreign body device inside the vessel, which can produce fracture or chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…DCB are becoming a promising endovascular tool, because they have the capacity of local drug transfer to the vessel wall, inhibiting cell proliferation and moderating the hypertrophic cell response to injury [6]. An additional benefit of DCB is that they do not leave any foreign body device inside the vessel, which can produce fracture or chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…4). Porous balloon: Oberhoff et al [43] studied the efficacy of paclitaxel using a porous balloon in carotid arteries of New Zealand White rabbits after development of an intimal plaque by electrical stimulation, cholesterol diet, and subsequent balloon angioplasty. Local drug delivery of paclitaxel (105 mol/L in 4 mL) was accomplished with a 2.5-mm long porous balloon catheter with 35 holes, (hole diameter 75 lm) using an injection pressure of 2 atm.…”
Section: Geniementioning
confidence: 99%
“…Moreover, a recently published study demonstrated the MR-guided delivery of a contrast media doped solution to the vessel wall using a standard balloon catheter with multiple perforations on a 1.5 Tesla scanner [14]. Perforated balloon catheters have been described in the literature [21,22]. However, coated balloons have achieved more acceptance over the years due to more homogenous drug distribution [7,8,18].…”
Section: Drug-coated Balloon Angioplastymentioning
confidence: 99%